Information asymmetry and bank regulation: Can the spread of debt contracts be explained by recovery rates? - Liu, Wenchien; Miu, Peter; Chang, Yuanchen; Ozdemir, Bogie (Journal of Financial Intermediation, 2012)
We investigate whether the spread of corporate debt contacts can be explained by their ultimate recovery rates. Using the actual realized recovery rates of defaulted debt instruments issued in the US from 1962 to 2007, we find that recovery rate is reflected in the spread at issuance, and that this relationship has become more significant since commercial banks were allowed to underwrite corporate securities. Our further investigation indicates that the enhanced informativeness of recovery rate can be attributed to the lowering of information asymmetry of individual firms. Besides, the relation between the spread at issuance and the recovery rate is stronger for weak corporate governance and non-investment grade issuers. Our conclusions are found to be robust to endogeneity issues, potentially omitted variables and alternative model specifications.